The Impact of Various Filling Patterns and Building Orientations on the Mechanical Characteristics and Building Time of PLA Using FDM - M. Hamoud; Sachin Salunkhe; Lenka Cepova; H. M. A. Hussien (International Journal of Polymer Science)
Fused deposition modeling (FDM) is a layered manufacturing (LM) process in which progressive 2D layers of material are kept making a 3D part. To optimize the building operation, the investigation is necessary to study the effect of process parameters. This study examines the impact of three filling patterns, “triangles,” “cross,” and “cross 3D,” with three filling densities (25%, 50%, and 75%) in three orientations (“flat,” “on long edge,” and “on short edge”) on ultimate tensile strength (UTS), hardness and the printing time of polylactic acid (PLA) material. This work built tensile specimens according to ASTM D638 on an open-source 3D printer. The UTS was collected using a WDW-2000 computer control electronic universal testing machine. The hardiness value was also measured using Shore A hardness durometers DIN 53505 and ASTM D2240. In addition, the building time was conducted by implementing the “Cura 4.6” slicer software. The results show that the filling pattern, orientation, and density at which the part is built significantly affect the strength, hardness, and building time. For light structure parts with 25% density, it is recommended to build parts with “triangles” “on long edge” to obtain the highest strength (31.02 MPa), which improved by 74.3%, with 281 HV at the minimum time (1 h:10 min), which was reduced by 46.1%. For dense structure parts, “triangles” and “on long edge” are recommended to give the highest strength (42.12 MPa), which can be improved by 69.8% (282 HV) at the minimum time (1 h:35 min), which was reduced by 36.2%. For medium construction, 50% of the parts can be built by the following parameters: “cross” and “on long edge” to obtain the highest strength (38.48 MPa) with 283 HV at the minimum possible time (1 h:55 min). The study could help with the growth of producing mechanically functional parts, such as prosthetics, using LM. In addition, the part can be built with high strength, hardness, and minimum building time, which is useful information for the best utilization of the 3DP machine. Also, the chosen parameters optimize the building process with little human intervention.